Unclean, Unseen: Social Media, Civic Action and Urban Hygiene in India. Issue 4 (1st October 2016) - Doron, Assa
ABSTRACT: Successive Indian governments have attempted to tackle the formidable task of creating a clean India, with varied results. With the country's rapidly growing middle class eager to participate in a sanitised global consumer capitalism, many Indians are becoming frustrated with the 'unruly' nature of their urban landscape, its dirty streets and public spaces. This is particularly discernible amongst India's middle-class youth, who seem impatient with the state's apparent inability to manage waste and disorder, and it is clear that several civil society campaigns designed to promote a clean India explicitly target Indian youth. In this paper, I explore what the ideological premise of cleansing initiatives reveals about the aspirations, needs and anxieties of India's youth. Abstract :